PELAKSANAAN PEMBELAJARAN REMEDIAL PADA MATA PELAJARAN SOSIOLOGI DI SMA N I HILIRAN GUMANTI KABUPATEN SOLOK - Fitri, Desi; Husnita, Liza; Anggreta, Dian Kurnia (Pendidikan Sosiologi, 2014)
The background of this research background by the large number of students who take remedial learning implementation in sociology in high school subjects SMA N I Gumanti fistula, after execution of remedial learning there is also students who score below the KKM. Learning the remedial efforts of the teacher is to provide assistance to students who have difficulty learning, which is expected to improve constraints in the learning process therefore the purpose of this study is to describe the implementation of remedial teaching in accordance with the KTSP. This research is a qualitative descriptive approach. techniques used in data collection observation, interviews, document study, informant selection techniques are purposive sampling where the samples were intentionally set by the researchers, sample selection based on necessity and sufficiency of research data, the accuracy of the data was tested by using triangulation of data and theories used in this research is the theory of structural fungsianalisme known as AGIL. The results of this study indicate that teachers do not make lesson planning remedial programs and implementation of remedial learning The SMA N I Gumanti fistula has not been fully implemented accordance with the following steps KTSP: 1. The diagnosis of student difficulties, teachers do not perform diagnostic difficulties students but teachers only perform diagnostic tests ie analyzing student learning outcomes. 2. The teacher does not provide remedial learning measures such as; re learning provision, provide specific guidance, the provision of training tasks in particular, use of peer tutoring, 3) timing of remedial learning 4) Retest, 5) Values of remedial results. Remedial learning yet achieving the goal of improve the way of teaching, learning, adjustment of the material and curing learning barriers faced by students, The main goal is complete the teacher values students who scored below the KKM.